Unloading freight at Skagway, 1898 - Curtis, Asahel, 1874-1941
Gold seekers heading to the Klondike gold fields via the Inland Passage could land at Skagway or Dyea. At first, ships had to anchor offshore and unload their passengers and freight onto barges which carried them ashore. There was usually an extra charge for this. This 1898 photo of the tidal flats at Skagway shows freight being unloaded from a barge. Horses and wagons stand by to carry freight and passengers into Skagway (out of sight to the left). The wooden pilings in the background will support the port's new piers. Original photograph: Curtis, Asahel, 1898. Copied after 1975 by the Museum of History and Industry. 1 negative: safety film, b&w; 2.5 x 3 in.